Legal Consequences for Perpetrators of Violations of The Economic Rights of The Creator and Efforts to Strengthen The Protection of a Song Copyright Work - Oksidelfa Yanto (Magister of Law, Faculty of Law, University of Mataram, 2022)
This study is purposed to determine the legal consequences for someone who commits copyright infringement, especially when the person commercially utilizes the economic rights of a song copyright work. It also wants to know what efforts can strengthen the protection of a song copyright work. The method used in this study is normative juridical method through literature study, with the presentation of data in the form of secondary data. The results showed that the legal consequences for perpetrators of violations of the economic rights of copyright works are punished with imprisonment for a maximum of four years and / or a maximum fine of Rp. 1.000.000.000. In the sanctions, parties other than the creator are prohibited from taking advantage of the economic rights of the creator. The effort to strengthen the protection of a song copyright work is to form a special body that will be in charge of preventing and eradicating all acts that violate the copyright of song works. Then no less important is to apply all the provisions of existing regulations firmly by all law enforcement officers, especially judges in each decision.